Exploitation of the Ugi 5-Center-4-Component Reaction (U-5C-4CR) for the Generation of Diverse Libraries of Polycyclic (Spiro)Compounds - Moni, Lisa; De Moliner, Fabio; Garbarino, Silvia; Saupe, Jörn; Mang, Christian; Basso, Andrea (Frontiers in Chemistry, 2018)
An Ugi multicomponent reaction with chiral cyclic amino acids, benzyl isocyanide and cyclic ketones (or acetone) has been exploited as key step for the generation of peptidomimetics. After a straightforward set of elaborations, the peptidomimetics were converted into polycyclic scaffolds displaying two orthogonally protected secondary amines. Libraries of compounds were obtained decorating the molecules through acylation/reductive amination reactions on these functional groups.